2015
DOI: 10.1007/s11760-015-0790-4
|View full text |Cite
|
Sign up to set email alerts
|

On an algorithm for Vision-based hand gesture recognition

Abstract: A vision-based static hand gesture recognition method which consists of preprocessing, feature extraction, feature selection and classification stages is presented in this work. The preprocessing stage involves image enhancement, segmentation, rotation and filtering. This work proposes an image rotation technique that makes segmented image rotation invariant and explores a combined feature set, using localized contour sequences and block-based features for better representation of static hand gesture. Genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown that the incidence of gestational diabetes and hypertension in pregnant women is getting higher and higher. Therefore, women during pregnancy and childbirth should increase their physical activity to maintain the health of themselves and their fetus [ 15 ].…”
Section: Yoga Postpartum Pelvic Floor Rehabilitation Methodsmentioning
confidence: 99%
“…Studies have shown that the incidence of gestational diabetes and hypertension in pregnant women is getting higher and higher. Therefore, women during pregnancy and childbirth should increase their physical activity to maintain the health of themselves and their fetus [ 15 ].…”
Section: Yoga Postpartum Pelvic Floor Rehabilitation Methodsmentioning
confidence: 99%
“…Mohanty [46] proposed a new hand-gesture recognition method that integrates multi-image features and multi-kernel learning SVM to improve the accuracy of multiclass handgesture recognition and generalize the algorithm. Ghosh [47] used two ASL (American sign language) datasets for static hand-gesture recognition, and through cross-validation of various recognition algorithms, the maximum dataset-1 (82.25%) and dataset-2 (87.67%) per dataset) confirmed the recognition accuracy. Oyedotun [48] discusses the use of deep learning in recognizing static hand gestures in vision-based systems.…”
Section: ) Rgb Cameramentioning
confidence: 93%
“…They considered different feature extraction methods and taken accuracy which is done on different signs, numbers, alphabets and words. (Ghosh & Ari, 2016) proposed LCS feature set with block-based feature and is applied for 24 static ASL Hand Alphabet and obtained 82% accuracy. (Sharma &Verma, 2015) used hand gesture shapes and positions recognition system and obtained an accuracy of 95.44%.…”
Section: Related Workmentioning
confidence: 99%